Lender of last report in a transitional economy with a fixed exchange rate: Financial crises and monetary policy in Sweden under the silver and gold standards, 1834 - 1913 - Anders Ögren (Stockholm School of Economics, The Economic Research Institute (EFI), 2003)
According to the classical view, an economy's lender of last resort should be its central bank. For brief periods of time, the bank might suspend convertibility in order to provide the liquidity needed to support the domestic credit market. Recent experience of financial crises demonstrates the conflict between maintaining a fixed exchange rate and serving as a lender of last resort. The lesson of Sweden's history of crises under the classical specie standard is that a transitional, capital importing economy has to pay closer attention to the specie standard rules than do capital exporting economies. While the Swedish central bank, for a limited time, could support the credit market within the limits of the specie standard, if the crises persisted support mechanisms other than abandoning convertibility were required. The solution adopted was to import high powered money through loans guaranteed by the Swedish State.
Keywords: E42; E58; N13; N23; 330; Classical silver and gold standards; Financial Crises; Fractional Reserves; Lender of Last Resort; Monetary Policy; Übergangswirtschaft; Fester Wechselkurs; Goldwährung; Silberwährung; Schweden; Finanzmarktkrise; Lender of Last Resort